Survey of activation‐induced genome architecture reveals a novel enhancer of Myc. Issue 4 (14th February 2023) - Chan, Wing Fuk; Coughlan, Hannah D; Ruhle, Michelle; Iannarella, Nadia; Alvarado, Carolina; Groom, Joanna R; Keenan, Christine R; Kueh, Andrew J; Wheatley, Adam K; Smyth, Gordon K; Allan, Rhys S; Johanson, Timothy M
Abstract: The transcription factor Myc is critically important in driving cell proliferation, a function that is frequently dysregulated in cancer. To avoid this dysregulation Myc is tightly controlled by numerous layers of regulation. One such layer is the use of distal regulatory enhancers to drive Myc expression. Here, using chromosome conformation capture to examine B cells of the immune system in the first hours after their activation, we reveal a previously unidentified enhancer of Myc . The interactivity of this enhancer coincides with a dramatic, but discrete, spike in Myc expression 3 h post‐activation. However, genetic deletion of this region, has little impact on Myc expression, Myc protein level or in vitro and in vivo cell proliferation. Examination of the enhancer deleted regulatory landscape suggests that enhancer redundancy likely sustains Myc expression. This work highlights not only the importance of temporally examining enhancers, but also the complexity and dynamics of the regulation of critical genes such as Myc . Abstract : In this article, we explored the three‐dimensional genome architectural changes in the genome of B cells in the hours after their activation. This revealed a previously undetected enhancer of the Myc gene. The interaction of this enhancer with the Myc promoter coincides with a dramatic, but discrete, spike in Myc expression 3 h post‐activation. However, genetic deletion of this region in mice, has little impact on Myc expression, Myc protein level or in vitro and in vivo cell proliferation, with enhancer redundancy likely sustaining Myc expression in the absence of the enhancer.